(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Congestion is the most important problem for private networks, one of this problem is the formation of routing rings when an error occurs in the operation of the routing algorithm between a set of nodes and the path to a particular destination is a loop that leads to cut the connection. In the present research we try to limit the formation of guidance rings and avoid congestion by proposing and evaluating the LLD and LMR methods to reduce the Interim loops. The foundation has been given a rationale for the loop prevention performance, and each methods was simulated using the program Qualnet 4.5 for simulation ad hoc network.